Respuesta :
Answer: The original rectangle was 15 inches by 6 inches
=============================================================
Explanation:
- L = original length
- W = original width
Let's make the length longer than the width, so L = W+9 since we're told that one side is 9 inches longer than another.
The area of this rectangle is
Area = length*width
A = L*W
Through substitution, we can replace L with W+9
A = (W+9)W
A = W^2 + 9W
We'll come back to this later.
--------------
Now let's decrease the longer side L by 5 inches to get L-5. At the same time, we'll increase the shorter side W by 3 to get W+3.
The new rectangle is (L-5) inches by (W+3) inches which leads to the area of...
A = (length)*(width)
A = (L-5)*(W+3)
A = (W+9-5)*(W+3) .... L replaced with W+9
A = (W+4)(W+3)
A = W^2 + 3W + 4W + 12 .... FOIL rule
A = W^2 + 7W + 12
--------------
We found these two area expressions
- W^2 + 9W
- W^2 + 7W + 12
We're told that the two areas (of the original and new rectangle) are equal to one another. Set them equal to each other and solve for W
W^2 + 9W = W^2 + 7W + 12
9W = 7W + 12 ............ subtracted W^2 from both sides
9W-7W = 12
2W = 12
W = 12/2
W = 6
The original width is 6 inches
L = W+9 = 6+9 = 15
The original length is 15 inches
The original area is L*W = 15*6 = 90 square inches
The new rectangle has side lengths of (L-5) = (15-5) = 10 inches and (W+3) = (6+3) = 9 inches. Then note how the area of this new rectangle is 10*9 = 90 square inches to match the other area. This helps confirm we have the correct answer.